New Perspectives on Interregional Interaction in Ancient Mesoamerica - Carrasco, Michael; Englehardt, Joshua (University Press of Colorado, 2019)
"Explores the role of interregional interaction in dynamic sociocultural processes that shaped the Pre-Columbian societies of Mesoamerica. Interdisciplinary scholars examine linguistic exchange and borrowing, scribal practices, settlement patterns, ceramics, iconography, and trade systems, presenting a variety of case studies drawn from multiple spatial, temporal, and cultural contexts"--Provided by publisher